Azithromycin vs. chloramphenicol for uncomplicated typhoid fever in children - Yulia Antolis; Tony Rampengan; Rocky Wilar; Novie Homenta Rampengan (Indonesian Pediatric Society, 2013)
Background The emergence of multiple-drug-resistantSalmonella typhi strains has made it necessary to evaluate newagents for the treatment of typhoid fever. Azithromycin has in vitroactivity against many enteric pathogens, including Salmonella spp.However, there is not enough evidence to compare azithromycinwith first-line antibiotics currently used.Objective To analyze the efficacy of azithromycin comparedto that of chloramphenicol as a first-line drug in the therapy ofuncomplicated typhoid fever in children.Methods We conducted a randomized open trial from November2011 to March 2012 on 60 children aged 2-13 years withuncomplicated typhoid fever. Subjects were randomly assignedto receive either azithromycin (10 mg/kgBW /day orally oncedaily) or chloramphenicol (100 mg/kgBW/day orally in fourdivided doses) for 7 days. Efficacy was measured by recordingclinical cures and fever clearance times. Data was analyzed withChi-square and T-tests.Results All of 30 patients in the azithromycin group and 28out of the 30 patients in the chloramphenicol group were cured(P= 0.246). Fever clearance time was shorter in the azithromycingroup (mean 37.9 (SD 32.75) hours, 95%CI 25.67 to 50.13)than in the chloramphenicol group (mean 49 (SD 45.83) hours,95%CI 3 1.89 to 66.11).Conclusions The efficacy of azithromycin is similar to that ofchoramphenicol in the treatment of uncomplicated typhoid feverin children. Azithromycin has shorter fever clearance time andhigher cure rate compared to those of chloramphenicol, althoughthese results are n ot statistically significant.